Needed to Regional Cooperation to Combat People Smuggling in Indonesian Waters - Chomariyah (Fakultas Hukum Universitas Hang Tuah, 2017)
People smuggling is a growing global crime that exposes thousands of migrants to unacceptable risks and challenges the integrity of international borders. In the last two decades, globalization and conflicts have seen an increase international migration flows. People smuggling is not a new phenomenon in Indonesia. It has developed steadily over the last 10 years in response to the increased demands of asylum seekers and refugees attempting to reach Australia by boat. Among the convicted people smuggling organizers are a number of rejected asylum seekers who stayed on in Indonesia for years. Some smugglers are former refugees but now hold Australian citizenship, granted to them after regular resettlement. Indonesia recorded nine boat accidents involving 728 asylum seekers in 2012, while in the following year the number rose to 23 involving 615 victims. Operation Sovereign Borders and they turn-back-theboats policy from Australia, from December 2013 to March 2014, there were seven occurrences of boats being turned back to Indonesian waters. The result of research show that first, Indonesian government need regional cooperation to handling treated people smuggling in Indonesian waters. Regional cooperation would be a win-win solution for both countries. And second, the regional cooperation should be in line with prevailing Indonesian legislation.